Combining mobile technologies in environmental education: a Greek case study. (2017) - Kalogiannakis, Michail; Papadakis, Stamatios
In recent years, due to the widespread use of Information and Communication Technologies (ICTs) various technological tools and services have found application in education. The education community has recognised that mobile devices and their applications can be used for environmental education as well as in education for sustainable development. Quick Response (QR) codes are an example as they successfully integrate mobile learning technology in Environmental Education. When attached to an object, the QR codes add a layer of digital functionality that transforms and expands the way users of mobile devices access the information without temporal-spatial restrictions. In the present study, we present a didactic approach that was implemented by High School teachers in the field of Environmental Education using mobile devices and QR codes.